The dynamics of sex-age structure of the population in urban and rural areas in the Republic of Kazakhstan in the years 1991-2013 - Nyussupova Gulnara; Kalimurzina Aisulu (Bulletin of Geography. Socio-Economic Series)
In this article we discuss and analyse changes in the sex-age structure of both the urban and the rural population of the Republic of Kazakhstan since independence (1991) and until 2013. Spatial analysis by age and sex was carried out for the urban and rural population of the Republic of Kazakhstan. The article focuses on the population of Astana and Almaty as cities of “republican subordination”. The aim of this article is to study and analyse the sex-age structure of the total population taking the urban and rural population from 1991 to 2013 separately. For comparison and analysis of statistical data in the dynamics, the data by sex and age of the urban and rural population for 1991, 2001 and 2011 were examined. Thus changes over 10 years are considered. The age groups for which the data were collected were based on differentiation of the population by economic status: pre-working (0-14 years), working (15-64), and post-working age (over 65 years).